Simultaneous occurrence of enterotoxigenic Staphylococcus aureus on the hands and in the mouth and stools of asymptomatic carriers - Andrade, Gildete Patriota de; Zelante, Flávio (Revista de Saúde Pública, 1989)
One hundred and twelve asymptomatic individuals were analysed with regard to the simultaneous incidence of Staphylococcus aureus on their hands and in their nose, mouth and stools, in the city of S. Paulo (Brazil). A total of 40 (35.7%) individuals were detected as carriers of this microorganism. Among these carriers, 27 (67.5%) were positive in only one of the four niches studied, 8 (20.0%) in two and 5 (12.5%) in three niches. They were identified 113 Staphylococcus aureus strains, and 28 (24.8%) of these strains, isolated from 9 (22.5%) carriers, produced enterotoxin. Of these strains, 7 (25.0%) produced type A enterotoxin, 6 (21.4%) of type B, 11 (39.3%) type C and 4 (14.3%) produced both type A and C. The phage typing of the 113 Staphylococcus aureus strains revealed the predominance of the strains lysed by phages belonging to the Group I/III/NC (16.8%). The results obtained did not demonstrate the simultaneous incidence of Staphylococcus aureus strains in samples collected from mouth, hands and stools of the group studied.